Domestic electronic ignition on spark ignition engines - Valderrama Romero, Andrés (1998)
The modification of the conventional ignition system by ruptor is presented, adapted and built from the Bosch and Delco Remy inductive ignition systems; obtaining the electronic ignition system. Experimental tests were carried out on the four-cylinder Ford engine located at the National University of Engineering, working in idle and load variation regimes, obtaining an increase in power, a decrease in fuel consumption and a decrease in toxic emissions. Translated with www.DeepL.com/Translator (free version)